2012
DOI: 10.1016/j.cbpc.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Copper effects on key metabolic enzymes and mitochondrial membrane potential in gills of the estuarine crab Neohelice granulata at different salinities

Abstract: The estuarine crab Neohelice granulata was exposed (96 h) to a sublethal copper concentration under two different physiological conditions (hyperosmoregulating crabs: 2 ppt salinity, 1 mg Cu/L; isosmotic crabs: 30 ppt salinity, 5 mg Cu/L). After exposure, gills (anterior and posterior) were dissected and activities of enzymes involved in glycolysis (hexokinase, phosphofructokinase, pyruvate kinase, lactate dehydrogenase), Krebs cycle (citrate synthase), and mitochondrial electron transport chain (cytochrome c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Amongst the different physiological and biochemical processes negatively correlated with Cu in aquatic organisms, we can cite glycolysis, Krebs cycle, ionic and osmotic regulation, acid-base balance, ammonia excretion, oxygen consumption, and growth. Most of these effects can be directly or indirectly associated with an insufficient aerobic production of energy to maintain cell metabolism and homeostasis (for references, see Lauer et al 2012). Due to the high reactivity of ionic (Bfree^) Cu, cells have developed complex and elegant mechanisms for shuttling Cu into, through, and out of cells as needed for its many critical reactions, without allowing free Cu to exert cytotoxic effects.…”
Section: Effects Of Individual Factors On Gene Expression In Kidneymentioning
confidence: 99%
“…Amongst the different physiological and biochemical processes negatively correlated with Cu in aquatic organisms, we can cite glycolysis, Krebs cycle, ionic and osmotic regulation, acid-base balance, ammonia excretion, oxygen consumption, and growth. Most of these effects can be directly or indirectly associated with an insufficient aerobic production of energy to maintain cell metabolism and homeostasis (for references, see Lauer et al 2012). Due to the high reactivity of ionic (Bfree^) Cu, cells have developed complex and elegant mechanisms for shuttling Cu into, through, and out of cells as needed for its many critical reactions, without allowing free Cu to exert cytotoxic effects.…”
Section: Effects Of Individual Factors On Gene Expression In Kidneymentioning
confidence: 99%
“…The high expression of PEPCK in muscle during 12-24 h could be a result of gluconeogenesis in the muscle during this time period. In a previous study, Wang (et al 2012) found reduction of free amino acids in the muscle of Eriocheir sinensis after salinity stress for 12 h. Free amino acid and glycerol can be used to maintain the glucose level in the tissue of crab Neohelice granulata through gluconeogenesis under hypo-osmotic stress (Lauer et al, 2012;Nery and Santos, 1993). As muscle is a pool of amino acids in crustaceans, it can function as a source of amino acid supply to other tissues (Wang et al, 2012) and the amino acid can be further converted to glycogen through gluconeogenesis (Ramamurthi et al, 1968;Rosas et al, 2001;Wang and Scheer, 1963).…”
Section: Transcriptional Response To Acute Salinity Stress Of Differementioning
confidence: 97%
“…However, Cu is toxic at elevated concentrations, potentially causing oxidative stress through reactive oxygen species (ROS) generation and inhibiting enzymes by blocking other cofactor sites (Grosell 2011). Adverse effects of Cu exposure in marine invertebrates include metabolic disruption, cytotoxicity, and neurotoxicity (Brown et al 2004;Lauer et al 2012). More specifically in copepods, Cu exposure may delay development and thus increase age at maturity (Sullivan et al 1983;Kwok et al 2008), reduce reproductive output (Reeve et al 1977;Fitzer et al 2013), and reduce foraging activity (Sharp and Stearns 1997).…”
Section: Introductionmentioning
confidence: 99%